Late bronze age pottery as indicator of the deposition temperatures of the Minoan pyroclastic products, Santorini, Greece. - Tema, E.; Pavlides, S.; Kondopoulou, D. (Bulletin of the Geological Society of Greece, 2013)
The Minoan eruption of Santorini volcano (Greece) took place in the Late Bronze Age (17th century BC) and produced a great volume of volcanic products that covered the whole island and buried every human settlement under meters of pyroclastic deposits. In this study we used thermal analysis of the magnetic remanence carried by pottery fragments buried under the pyroclastic deposits in order to estimate the thermal effect of the Minoan volcanic products on the pre-eruption habitation level. A total of 70 samples, prepared from 45 independent pottery fragments, have been studied. Samples were collected from three different sites, situated at the southern part of the island. Stepwise thermal demagnetizations reveal that the pottery fragments generally carry a two-component remanent magnetization. Interpretation of the demagnetization results using the normalised intensity decay curves and the orthogonal projection diagrams indicates that most samples were re-heated at temperatures around 160-260o C. The obtained results represent the equilibrium temperatures reached after the deposition of the pyroclastic fall and show that the pyroclastic fall deposits at distances around 6 to 9 km from the eruption vent were still hot enough to reheat the buried pottery at such temperatures.